Kilwa, la cité de l'or africain - Pradines, Stéphane (Archéologia, 2006)
Keywords: Archéologie -- Kilwa

The Chronology of Kilwa Kisiwani, AD 800–1500 - Horton, Mark; Olsen, Jesper; Fleisher, Jeffrey; Wynne-Jones, Stephanie (The African Archaeological Review, 2022)
In this article, we present the results of a recent program of high-resolution radiocarbon dating on the urban sequence at Kilwa Kisiwani in southern Tanzania, including Bayesian modeling of 21 calibrated 14C dates. These data come from the 2016 excavation of a large trench directly adjacent to trench ZLL, one of the key 1960s excavations that served to establish the original chronology of the town. The new sequence reported here anchors the phases of Kilwa’s development for the first time in absolute terms. The dates, stratigraphy, and artifact assemblage offer a number of new insights into the timing and tempo of the occupation at Kilwa, notably placing the first coral buildings and coins at the end of the tenth century. Insights also include findings related to the earliest phases of settlement and periods of possible urban decline. We argue against a trend for understanding Swahili towns according to a common coastal trajectory and suggest that it is important to consider regional diversity by recognizing the particular, episodic sequence at Kilwa.
Keywords: Archéologie -- Kilwa